Vaccination Programmes Epidemiology, Monitoring, Evaluation - Hahné, Susan (Taylor & Francis, 2022)
Vaccination programmes are of vital importance to public health and are present in virtually every country in the world. By promoting an understanding of the diverse effects of vaccination programmes, this textbook discusses how epidemiologic methods can be used to study, in real life, their impacts, benefits and risks. Written by expert practitioners in an accessible and concise style, this book is interspersed with practical examples which allow readers to acquire understanding through real-life data and problems. Part I provides an overview of basic concepts in vaccinology, immunology, vaccination programmes, infectious disease transmission dynamics, the various impacts of vaccination programmes and their societal context. Part II covers the main field tools used for the epidemiological evaluation of vaccination programmes: monitoring coverage and attitudes towards vaccination, surveillance of vaccine-preventable diseases and pathogens, seroepidemiological studies, methods to assess impact and outbreak investigation. Part III is dedicated to vaccine effectiveness and its assessment. Part IV includes an overview of the potential risks of vaccination and how to study these. Lastly, Part V deals with methods for an integrated assessment of benefits and risks of vaccination programmes. Suitable for professionals working in public health, epidemiology, biology and those working in health economics and vaccine development, Vaccination Programmes also serves as a textbook for postgraduate students in public health, epidemiology and infectious diseases. The book is aimed at all those involved in the many aspects of vaccination programmes, including public health professionals and epidemiologists. Its primary target audiences are master and doctoral students in infectious disease epidemiology and public health, post-doctoral participants of field epidemiology training programmes and public health professionals working in the post-implementation epidemiological evaluation of vaccines and vaccination programmes.